2014
DOI: 10.1371/journal.pone.0088106
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hepatitis E Virus Infections among Swine, Swine Farmers and the General Population in Guangdong Province, China

Abstract: Hepatitis E virus (HEV) infection is widespread in China, but few studies have been carried out in Guangdong Province. This study aimed to characterize the prevalence of HEV infections among swine, swine farmers and the general population in Guangdong Province. We conducted an epidemiological study that included swine, swine farmers and health examination attendees in Guangdong from 2011 to 2013. The overall seroprevalence of anti-HEV antibodies in swine was 64.7%. The results revealed that growing pigs, sows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 35 publications
6
34
0
1
Order By: Relevance
“…This study, therefore, aimed at estimating the seroprevalence and risk factors of HEV infection in the Korean, Manchu, Mongol, and Han ethnic groups. The data showed that the seroprevalence of HEV infection in surveyed regions was 19.87% in this study, which was lower than the value of 23.30% in Jiangsu province, 38.34% in Guangdong province, 39.90% in Yunnan province, higher than the prevalence of 15.66% in xinjiang autonomous region, and similar to the 19.47% seroprevalence in Gansu province, China . Recently, some countries adjacent to China also reported the prevalence of HEV infection in local populations, such as 23.0% in Thailand, 9.4% in Korea, 14.4% in India, and 1/15 075 by detecting HEV‐RNA in Japan .…”
Section: Discussionsupporting
confidence: 47%
“…This study, therefore, aimed at estimating the seroprevalence and risk factors of HEV infection in the Korean, Manchu, Mongol, and Han ethnic groups. The data showed that the seroprevalence of HEV infection in surveyed regions was 19.87% in this study, which was lower than the value of 23.30% in Jiangsu province, 38.34% in Guangdong province, 39.90% in Yunnan province, higher than the prevalence of 15.66% in xinjiang autonomous region, and similar to the 19.47% seroprevalence in Gansu province, China . Recently, some countries adjacent to China also reported the prevalence of HEV infection in local populations, such as 23.0% in Thailand, 9.4% in Korea, 14.4% in India, and 1/15 075 by detecting HEV‐RNA in Japan .…”
Section: Discussionsupporting
confidence: 47%
“…9,10 In the present study, the median age of patients was 57.5 years (10e78 years) and the gender ratio of male-to-female was 4.64:1. The possible reasons for this pattern of disease remain to be determined, but may involve diet and/or immune status.…”
Section: Discussionmentioning
confidence: 52%
“…As shown in Figure , a total of 1987 studies were initially found in CNKI, PubMed and OVID, in which 234 studies were potentially related to our study objectives and had a full text retrieved. Subsequently, 204 studies were excluded with reasons listed in Figure , and two studies were added in an updated search, yielding 32 studies for the meta‐analysis (Bouwknegt et al, ; Caruso et al, ; De Sabato et al, ; Drobeniuc et al, ; Engle, Yu, Emerson, Meng, & Purcell, ; Galiana, Fernandez‐Barredo, Garcia, Gomez, & Perez‐Gracia, ; Hinjoy et al, ; Hongwei, ; Jiang, Zheng, & Shijuan, ; Kang et al, ; Krumbholz et al, ; Lange et al, ; Lee et al, ; Liang et al, ; Liu et al, ; Love, Bjornsdottir, Olafsson, & Bjornsson, ; Lu et al, ; Masia et al, ; Meng et al, ; Nong, Li, & Yi, ; Olsen, Axelsson‐Olsson, Thelin, & Weiland, ; Silva et al, ; Traore et al, ; Utsumi et al, ; Vivek & Kang, ; Wu, Liao, Wang, Lou, & Wenzhong, ; Wu, Xie, et al, ; Yan et al, ; Yu et al, ; Zheng et al, ). Of the included studies, 24 were published in English and eight in Chinese.…”
Section: Resultsmentioning
confidence: 99%